The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0110048
|View full text |Cite|
|
Sign up to set email alerts
|

The Extracellular Domain of Myelin Oligodendrocyte Glycoprotein Elicits Atypical Experimental Autoimmune Encephalomyelitis in Rat and Macaque Species

Abstract: Atypical models of experimental autoimmune encephalomyelitis (EAE) are advantageous in that the heterogeneity of clinical signs appears more reflective of those in multiple sclerosis (MS). Conversely, models of classical EAE feature stereotypic progression of an ascending flaccid paralysis that is not a characteristic of MS. The study of atypical EAE however has been limited due to the relative lack of suitable models that feature reliable disease incidence and severity, excepting mice deficient in gamma-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As an NHP model for immune‐mediated CNS disease, atypical EAE does have advantages, as disease can be induced, is self‐limiting, stable, and does not progress to humane endpoints like JME. However, there are distinct differences, specifically atypical EAE is associated with robust IgG response to conformational MOG epitopes, whereas JME exhibits positive CSF finding that have not yet been further evaluated for myelin specificity 3,12 . Interestingly, although we isolated and detected JMRV in JME lesions, we have not detected anti‐JMRV antibodies in the CSF, implying that CSF IgG targets other antigens.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As an NHP model for immune‐mediated CNS disease, atypical EAE does have advantages, as disease can be induced, is self‐limiting, stable, and does not progress to humane endpoints like JME. However, there are distinct differences, specifically atypical EAE is associated with robust IgG response to conformational MOG epitopes, whereas JME exhibits positive CSF finding that have not yet been further evaluated for myelin specificity 3,12 . Interestingly, although we isolated and detected JMRV in JME lesions, we have not detected anti‐JMRV antibodies in the CSF, implying that CSF IgG targets other antigens.…”
Section: Discussionmentioning
confidence: 61%
“…And second, EAE is studied primarily in inbred mouse strains and this is in large contrast to MS, which occurs in a heterogeneous population with highly variable genetic diversity. More recently, however, others have shown that induction of EAE with recombinant myelin oligodendrocyte glycoprotein (MOG) encoding the extracellular domain (aa 1‐170) or MOG encephalitic peptide (aa 34‐56) emulsified in incomplete Freund’s adjuvant in cynomolgus macaques ( Macaca fascicularis ) can lead to atypical EAE disease that displays heterogeneity in clinical course, including less progressive disease accompanied with periods of remission 3 . Additionally, atypical EAE disease in macaques includes comparable MRI results, demyelination, and MOG‐specific T‐cell proliferation resulting in Th1 and Th17 responses 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the results obtained from the induction of the Lewis rats model follow those in the literature. Histopathological aspects such as leukocyte infiltration, microglia activation, and the presence of demyelinated plaques are classic demonstrations of induction [ 23 , 24 ]. Thus, the indirectly proportional relationship between clinical score increases, as well as the reduction in the weight of induced animals [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further immunization protocols include immunization with the rat immunoglobulin variable (IgV)–related extracellular domain of myelin oligodendrocyte glycoprotein (IgV‐MOG) in CFA followed by one or more injections of rat IgV‐MOG in incomplete Freund's adjuvant (IFA). The resulting atypical disease was marked by torticollis, unilateral rigid paralysis, forelimb weakness, and high titers of anti‐ MOG antibody against conformational epitopes of MOG (Curtis et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…CFA + PT Antigen-specific T cells plus demyelinating anti-MOG Ab cause severe active disease Adelmann et al, 1995;Kojima et al, 1994;Linington et al, 1993 High-dosage PLP (1000 μg/rat) d CFA Monophasic active EAE Chalk et al, 1994 IgV-MOG e CFA + IgV-MOG injections + IFA Atypical EAE Curtis et al, 2014 Guinea pig MBP in Gimap5 mutant Lewis rats CFA T cell-mediated EAE despite lymphopenia Fischer et al, 2016 a The MBP-induced, Lewis rat model of EAE is commonly used as a model for an acute demyelinating attack in MS or acute disseminated encephalomyelitis. A central combined with a peripheral demyelination in the ventral and dorsal nerve roots has been reported (Pender, 1987;Pender, Tabi, Nguyen, & McCombe, 1995).…”
Section: Introductionmentioning
confidence: 99%